Consummatio gloriae – zapomniany Tomaszowy motywwcielenia Chrystusa w świetle ST II-II, q.2, a.7 - Piotr Świerczyński (Warszawskie Studia Teologiczne)
St. Thomas Aquinas wrote in ST II-II, q.2, a.7., that the first man could get know about Incarnation of Christ in future. The way of knowing of that is experience of marriage, witch is described by St. Poul as „great mystery”, „concerning Christ and the church” (Eph 5). In Thomas’s Commentary on St. Paul’s Epistle to the Ephesians we can read, that this link between husband-wife relation and Christchurch relation was known for the first man by supernatural knowledge. Before Summa Thomas wrote that the first man could have unclear knowledge about Incarnation: if man strays, God will want repair it, because it is result of his mercy (Commentary on the Sentences Book) or providence (De Veritate). In ST this clear knowledge is only about this aspect of Incarnation mystery, with is linked with Consummatio gratiae; the first man didn’t know about passion and death of Christ, because he couldn’t know about his own sin in future: their reason. Consumaatio gratiae means the full unite man with God in the end of the world and it’s coresponding with sexual intercourse in marriage. This motive for the Incarnation is not linked with men’s sin. It is in opposition to the view from ST III, q.1, a.3, corp., where St. Thomas wrote that if man had not sinned, the God would not have become incarnate, because everywhere in Sacred Scripture the sin of the first man is assigned as the reason for the Incarnation.